THE INFLUENCE OF COMMUNICATION AND MOTIVATION ON EMPLOYEE PERFORMANCE - Andi Sopandi; Ninik Anggraini; Ali Zaenal Abidin (Asosiasi Dosen Muda Indonesia, 2024)
This research aims to determine the effect of communication and motivation on employee performance at PT. Polarin Xinindo both partially and simultaneously. The method used is the Quantitative Associative method. The population in this study were employees of PT. Polarin Xinindo. The sampling technique used was the saturated sample method with 60 respondents. The data analysis method uses multiple linear regression tests. This research shows that communication has a positive and significant influence on employee performance. Work motivation has a positive and significant influence on employee performance. Simultaneously, communication and work motivation positively and significantly influence employee performance.